2012
DOI: 10.1080/1750984x.2011.631026
|View full text |Cite
|
Sign up to set email alerts
|

Music in the exercise domain: a review and synthesis (Part I)

Abstract: Since a 1997 review by Karageorghis and Terry, which highlighted the state of knowledge and methodological weaknesses, the number of studies investigating musical reactivity in relation to exercise has swelled considerably. In this two-part review paper, the development of conceptual approaches and mechanisms underlying the effects of music are explicated (Part I), followed by a critical review and synthesis of empirical work (spread over Parts I and II). Pre-task music has been shown to optimise arousal, faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
293
3
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 355 publications
(327 citation statements)
references
References 66 publications
16
293
3
15
Order By: Relevance
“…The mechanisms underlying the effects of music were expounded in a recent two-part review paper (Karageorghis & Priest, 2012a, 2012b therefore only an overview will be provided here: The limited capacity of the nervous system has a bearing on the effects of music on attention (see Rejeski, 1985). These limitations restrict the degree to which the human organism is able to process music during high-intensity activity when fatigue-related signals overwhelm the afferent nervous system.…”
Section: Mechanisms Underlying the Effects Of Music During High-intenmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms underlying the effects of music were expounded in a recent two-part review paper (Karageorghis & Priest, 2012a, 2012b therefore only an overview will be provided here: The limited capacity of the nervous system has a bearing on the effects of music on attention (see Rejeski, 1985). These limitations restrict the degree to which the human organism is able to process music during high-intensity activity when fatigue-related signals overwhelm the afferent nervous system.…”
Section: Mechanisms Underlying the Effects Of Music During High-intenmentioning
confidence: 99%
“…Psychophysical effects concern the reduction of perceptions of physical effort, which, in the music-related literature, are most often assessed using ratings of perceived exertion (RPE). Ergogenic effects relate to the use of music to improve physical performance by either delaying fatigue or increasing work capacity; this results in higher-than-expected levels of endurance, power, productivity, or strength (see Terry & Karageorghis, 2011).Extant work has shown that music use is not effective for some people under certain circumstances (e.g., while learning new skills) and might even be contraindicated in some instances (e.g., when it might distract users from safety-relevant information, such as on public roads; see Karageorghis & Priest, 2012a, 2012b for a review). Also, a "vitamin model" wherein a particular piece of music can be prescribed to engender certain perceptual, cognitive, or emotional responses in a listener, does not apply to this field of scientific endeavour (Sloboda, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A slow tempo will benefit an endurance exercise, 16 and a fast tempo will improve the work load during exercise. 17 Moreover, listening to music was demonstrated to be beneficial in various situations such as during physical exercise, 15,18 physiotherapy sessions for subjects with cystic fibrosis, 19 and rehabilitation of elderly subjects. 20 To our knowledge, its effect was not investigated during a group pulmonary rehabilitation session.…”
Section: Introductionmentioning
confidence: 99%
“…By analogy, pain perception is improved by focusing attention away from the painful stimulus. 14 The effect of music on psychologically modulated factors (mood, emotion, dyspnea) was investigated previously 15 and was related to its tempo according to the type of exercise. A slow tempo will benefit an endurance exercise, 16 and a fast tempo will improve the work load during exercise.…”
Section: Introductionmentioning
confidence: 99%